THE UTILIZATION OF THE FEHRING'S MODELS IN THE VALIDATION OF NURSING DIAGNOSES - Zeleníková, Renáta; Žiaková, Katarína (Profese Online, 2010)
It is important to validate nursing diagnoses to be appropriate to every socio-cultural context, but only little attention is paid to the accuracy of diagnosis. (Lunney, 2008, p. 29; Lunney, 2003, p. 96) The presumption of the high-quality research in the validation of nursing diagnoses is a well-done methodology, which should contribute towards providing a quality nursing care and effectiveness of nursing interventions. The aim of this article is to describe the Fehring's models of validation of nursing diagnoses, their advantages and disadvantages, and how they are used in validation studies. Fehring, as one of the renowned authors, offers the precisely broken-down methodology of the validation of nursing diagnoses. The analytical-synthetical approach was selected for the inquiry into the Fehring's models. Fehring's works were analyzed as well as the validation studies, in which one of his models was used.
Keywords: validation; validation study; nursing diagnosis; Fehring's validation models